The axiology of knowledge in response to the humanistic cloning system: in response to the humanistic cloning system - Jannah, Latifa Izzatul; Sari, Alvina Kumala; Safira, Izza; Arfani, Muhammad Azka; Bukhori, Ahmad (Maliki Interdisciplinary Journal, 2026)
Human cloning as a form of revolution in biotechnology in the 21st century raises complex ethical dilemmas that test humanistic principles such as dignity, autonomy, and welfare, as discussed by Suryanti (2019) and Muchtar (2014). This study aims to analyze the values in biotechnology knowledge in relation to cloning through an integrative humanistic perspective. The method used is a literature study from various disciplines, involving the collection of literature from the philosophy of science, bioethics, sociology of knowledge, and Islamic studies. The analysis was conducted using a descriptive critical approach and thematic synthesis. The results of the study show that there is tension between scientific development and humanism, with high medical risks (Wargasetia, 2010), violation of clone autonomy (Mutik & Suciptaningsih, 2024), eugenic exploitation (Sibarani, 2024), as well as interference with human nature and lineage according to Islam (Prawira et al., 2022). Reproductive cloning is considered contrary to universal human values. The implications of this research recommend a strict moratorium, regulations based on a value framework, and interdisciplinary dialogue between scientists, ethicists, scholars, and policymakers to steer biotechnology toward social justice and intergenerational solidarity.